Implementation of Bride and Groom Courses In North Balantak District, Banggai Regency In The Perspective Decision of The Director General of Islamic Community Guidance Number 379 of 2018 - Jarudin, Jarudin; Yamani, Gasim; Jumat, Gani; Raden, Sahran (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2023)
Implementing the Sakinah family movement program has improved and strengthened people's lives. This program then became a national movement that has grown and developed strong roots in friendly, polite, and peaceful Indonesian society. Despite its success, it turns out there are still severe problems, such as the high divorce rate, the large number of applications for marriage registration, the increase in domestic violence, and unregistered marriages. In the bride and groom course, pre-marital guidance participants gain knowledge and skills as preparations for entering a new household. The main problem of the research is what the process of implementing the bride and groom course looks like in the North Balantak sub-district, Banggai Regency. This research aims to determine the process of implementing the bride and groom course to find out how the review of the Director General of Islamic Community Guidance Number 379 of 2018 regarding the process of implementing the bride and groom course in North Balantak sub-district, Banggai district. The method used is qualitative research with data collection techniques through observation, interviews, and documentation. Using the theoretical basis of John McLeod's counseling and the Social Welfare of Harold L. Wilensky and Charles N. Lebeaux. Research results (1). Coaching consists of three stages: the first is coaching at the Religious Affairs office, the second is coaching at the Community Health Center, and the third is further coaching. (2) the review of the first Director General's Decree 379/2018 has not been maximal, and the second, according to the third regulation, still needs to be implemented—conclusion (1). Coaching is divided into three stages. (2) Review of Director General's Decree 379/2018. 1. Still needs to be optimal; 2. Compliant with regulations; 3. has not run.